An early warning indicator of mortality risk in patients with COVID-19: the neutrophil extracellular traps/neutrophilic segmented granulocyte ratio - Wang, Qiong; Qin, Yu; Ma, Jingyun; Zhou, Kehao; Xia, Guiping; Li, Ya; Xie, Li; Afful, Richmond Godwin; Lan, Qian; Huo, Xingyu; Zou, Jian; Yang, Hailin (Frontiers in Immunology, 2024)
Background: Neutrophil extracellular traps (NETs) play a key role in thrombus formation in patients with coronavirus disease 2019 (COVID-19). However, the existing detection and observation methods for NETs are limited in their ability to provide quantitative, convenient, and accurate descriptions of in situ NETs. Therefore, establishing a quantitative description of the relationship between NETs and thrombosis remains a challenge. Objective: We employed morphological observations of blood cells and statistical analyses to investigate the correlation between the NETs/neutrophilic segmented granulocyte ratio and mortality risk in patients with COVID-19. Methods: Peripheral blood samples were collected from 117 hospitalized patients with COVID-19 between November 2022 and February 2023, and various blood cell parameters were measured. Two types of smudge cells were observed in the blood and counted: lymphatic and neutral smudge cells. Statistical data analysis was used to establish COVID-19 mortality risk assessment indicators. Results: Morphological observations of neutrophilic smudge cells revealed swelling, eruption, and NETs formation in the neutrophil nuclei. Subsequently, the NETs/neutrophilic segmented granulocyte ratio (NNSR) was calculated. A high concentration of NETs poses a fatal risk for thrombus formation in patients. Statistical analysis indicated that a high NNSR was more suitable for evaluating the risk of death in patients with COVID-19 compared to elevated fibrinogen (FIB) and D-dimer (DD) levels. Conclusions: Observing blood cell morphology is an effective method for the detection of NETs, NNSR are important markers for revealing the mortality risk of patients with COVID-19.